Variations in morphological, biochemical and phytochemical traits of diploid and induced tetraploid plants of downy thorn-apple (Datura innoxia Mill.) - Parisa Naderian; Nasrin Moshtaghi; Abdolreza Bagheri; Saeed Malekzade Shafaroudi (Institue of Medicinal Plants, ACECR, 2022)
Background: Datura species produce a wide range of tropane alkaloids with medicinal values. D. innoxia is a species of the Datura genus which is poisonous and has an unpleasant odor due to the presence of tropane alkaloids. Objective: The study aimed to induction of polyploidy by colchicine treatment on downy thorn-apple and the effect of it on appearance and hyoscyamine content. Methods: In order to induce tetraploidy in downy thorn-apple, a factorial experiment was carried out with two factors: colchicine concentrations (0.05, 0.1, and 0.2 %) and exposure time (48 and 72 h) with 3 plants for each treatment with using a cotton ball included colchicine on shoot tip. Morphological changes were observed and the plants were analyzed by flow cytometry in near to the flowering time. Results: The results showed that the concentration and exposure time of colchicine, and their interaction affected the percentage of tetraploidy. The maximum percent of tetraploidy was observed in concentration of 0.2 % and 72 h. On the other hand, the application of different concentrations of colchicine and exposure time didn't have a significant effect on plant survival. The number of stomatal guard cells were decreased but no significant differences were observed in the content of total chlorophyll and carotenoids. Also, the hyoscyamine content in tetraploid plants was decreased to half in comparison to diploid ones. Conclusion: In general, induction of tetraploidy in this plant could change some phenotypic traits but has a negative effect on hyoscyamine content.